Automated fastener versus manually tied knots in minimally invasive mitral valve repair: impact on operation time and short- term results. Issue 1 (December 2015) - Grapow, Martin; Mytsyk, Miroslawa; Fassl, Jens; Etter, Patrick; Matt, Peter; Eckstein, Friedrich; Reuthebuch, Oliver
Abstract Background This study compares the influence of two different annuloplasty attachment suture applications, namely the use of an automated fastener versus manually tied knots using a traditional knot pusher, on total operation time, on cardiopulmonary-bypass time and on cross-clamp time, and on short-term outcome. Methods Sixty patients underwent isolated minimally invasive mitral valve repair in Carpentier Type-II mitral disease with implantation of an annuloplasty ring in combination with correction of the prolapsing leaflet using artificial chords. The first 30 patients after implementation of a novel automated fastener were compared with the last 30 patients corrected with a traditional knot pusher. No significant differences with regard to demographic data (age, gender, NYHA class, ejection fraction, BMI, cardiovascular risk factors) between the two groups were found. All patients received isolated mitral valve repair in the first run. Bretschneider HTK was used for cardioplegic cardiac arrest in all patients. Results Transesophageal and transthoracic echocardiography at the end of operation and at discharge revealed no (n = 25), trace (n = 28) or mild (n = 7) residual regurgitation with no evidence of ring dehiscence and without any significant clinical differences between the groups. Cross-clamp, cardiopulmonary-bypass and total- operation time were significantly reduced in the automated fastener group compared to the group using a traditional knot pusher (87.1 ± 17.9 vs. 101.3 ± 17.8;p < 0.01, 138.1 ± 25.6 vs. 152.7 ± 24.9;p < 0.05, and 203.9 ± 31.02 vs. 223.8 ± 29.01;p < 0.01, respectively). Conclusion Our short-term results indicate a safe, reliable and fast application of the novel automated fastener device in combination with significant time savings in cardioplegic arrest and cardiopulmonary bypass.